Microzonation Analysis of Soil Vulnerability Index of Sumani Region As Part of The Sumatra Fault System Using Microtremor: Analisis Mikrozonasi Indeks Kerentanan Tanah Daerah Sumani Sebagai Bagian Dari Sistem Sesar Sumatera Menggunakan Metoda Mikrotremor - Lingga Ayunda Pradipta; Syafriani Syafriani; Hamdi Hamdi; Letmi Dwiridal (Department of Physics, Universitas Negeri Padang, 2023)
West Sumatra is a province located on the west coast of the island of Sumatra in the middle which has four active fault segments. Nagari Sumani is part of the Sumani Segment line, which makes Nagari Sumani very vulnerable to earthquakes. Efforts are needed too . reduce the impact of the earthquake in Nagari Sumani. This study aims to determine the value of soil vulnerability index (Kg) and soil vulnerability index microzonation (Kg) in Nagari Sumani, specifically Jorong Pinjangek and Jorong Guci, in the area of ​​the Sumani Segment route. The microtremor method of measuring this microtremor can determine the dominant frequency value (f0), amplification factor (A0), and soil susceptibility index value (Kg). Microtremor data was used to obtain the H/V curve at each point of data collection using Geopsy software. Seismic vulnerability index microzonation is carried out using software Surfers 13. The results of this study indicate that the seismic vulnerability index in Nagari Sumani ranges from 3.65 x 10-6 s2/cm to 99.51 x 10-6 s2/cm which has low, medium, to high categories. The results of microzonation of low soil susceptibility index (Kg) are at points 1,2,7, and 8 with a value range of 3.65 x 10-6 s2/cm to 41.02 x 10-6 s2/cm, the medium category is in points 3 and 5 with a value range of 50.02 x 10-6 s2/cm to 54.23 x 10-6 s2/cm, while the high category is at points 4 and 6 with a value range of 63.32 x 10-6 s2/cm to 99.51 x 10-6 s2/cm .